Welcoming Guests in Indonesian Traditions: Cultural Studies in Minang, Bugis, Palembang, and Surakarta Dance - Gunawan Wiradharma; Sri Sediyaningsih; Zul Fahmi; Mario Aditya Prasetyo; Cicilia Clara Devi Anggraini (PERSPEKTIF, 2023)
The culture of several regions in Indonesia has a tradition of welcoming guests in the form of traditional dance performances. This study intends to find out the traditions and developments of the welcoming dance at this time. In addition, this study suggests reasons why guests need to be presented with a performance in Minang, Bugis, Palembang and Javanese culture. This research reveals values ​​and meanings so that the characteristics and developments that a culture can carry out in honoring guests can be identified. The method used is qualitative by conducting in-depth interviews with traditional Minang, Bugis, Palembang and Solo artists. The findings in this study indicate that the main motive for guests to be respected and exalted in an area is because guests are considered "kings" by the four cultures. The context of being “raja” refers to two things: First, because this dance is really danced to welcome the king, as explained in the Paduppa, Selik Tubu and Gambyong dances. Second, the term "king" is just a parable so that the guests are treated as best as possible like a king. When the guests are "kingled", it is hoped that they will establish good relations and return to visit the area. This good relationship is symbolized by giving banquets to guests, such as cake, betel, gambir, tambakau, areca nut. By experiencing this banquet, it is hoped that the guests will also feel the bitterness of life that is felt by the community, so that later it will foster a sense of sympathy and empathy for the guests to uphold mutual respect and respect for one another.